2019
DOI: 10.12659/msm.917207
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl Disulfide Mitigates DNA Damage and Spleen Tissue Effects After Irradiation

Abstract: BackgroundSeveral factors found in foods are beneficial to human health and they may contribute to radiation protection. Taking food factors could be an easy way to reduce the effects of radiation after nuclear accidents, as well as secondary radiation risks after cancer radiotherapy or space missions. Here, diallyl disulfide (DADS), a component of garlic oil, was studied for its ability to mitigate radiation damage.Material/MethodsWe investigated the effects of DADS on micronucleus (MN) formation and apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Hetal [60] also found that exposure to benzene damages liver tissues significantly, resulting in necrosis and sinusoidal dilatation. The agent's ability to damage DNA is to the many splenic lesions found in this study [61].…”
Section: Discussionmentioning
confidence: 67%
“…Hetal [60] also found that exposure to benzene damages liver tissues significantly, resulting in necrosis and sinusoidal dilatation. The agent's ability to damage DNA is to the many splenic lesions found in this study [61].…”
Section: Discussionmentioning
confidence: 67%
“…The survival time and body weight of the IR+WHPs-M mice were greater than those of the IR+whey protein group mice, indicating that peptides play a better role than intact protein in the nutritional support of irradiated mice. In addition, we found that the relative weight of the spleen in IR+whey group mice increased 14 days after radiation, suggesting that whey protein supplementation may cause spleen inflammation, but WHPs did not [ 17 ]. Interestingly, the effects of WHPs on survival time and body weight did not follow a dose-response relationship.…”
Section: Discussionmentioning
confidence: 99%